Impor gandum Indonesia dan faktor-faktor yang Mempengaruhinya - Wulandari, Gita; Hodijah, Siti; Vyn Amzar, Yohanes (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims: 1) to analyze the development of wheat import volume, gross domestic product (GDP), inflation, investment credit interest rates, and population of Indonesian wheat imports. 2) to analyze the effect of gross domestic product, inflation, investment interest rates on Indonesian wheat imports. This study is a descriptive study and the types of data used in this study are secondary data in the form of gross domestic product, inflation, investment credit interest rates, and population for the last 18 years (2000-2017). The data obtained were processed using SPSS 20 with multiple linear regression models using the Ordinary Least Square (OLS) method. The results of this study indicate that the gross domestic product (GDP) obtained a significant level of 0.03, inflation obtained a significant level of 0.598, and the total population obtained a significant level of 0.522. The regression results show that partially only the variable gross domestic product (GDP) and interest rates are Investment credit interest has a significant effect on imports of Indonesian wheat, while inflation and population have no significant effect on imports of Indonesian wheat. Keywords: GDP, Inflation, Interest rates, Population